Empowering Micro Small Medium Enterprises Human Resources Through Training: A Case Study of MSME in Cianjur, West Java-Indonesia - Fahriyah, Aramia; Chairani, Ridfa; Sudinta, Heru; Irwansyah, Iwan (Technium Social Sciences Journal, 2021)
The number of Micro Small Medium Enterprises (MSME) in Indonesia continues to show an increase, but unfortunately this is not followed by an improvement in the quality of human resources who manage MSMEs. This study aims to answer questions about what problems are faced by MSMEs in Cianjur area related to human resources, and how to improve the quality of MSME human resources so that the products they produce have the quality to compete with other products. This is a qualitative research with a case study approach. Data was collected through semi-structured interviews and in a fluid atmosphere. In this study, interviews were conducted with 10 MSME managers who had obtained credit from banks. This research shows that training for MSME managers needs to be carried out more intensively and the quality of training needs to be improved so that the goals and targets for improving the skills of MSME managers can be achieved. Improvements in training that need to be done are in terms of the training preparation stages, namely by assessing training needs, designing a training program that suits the needs of participants, training implementation stage, and evaluating the training, so that the goals and objectives can be achieved. However, whatever the technical needs required by the trainees, the topics related to Behavior and Motivation must be given because this will be a driving force for MSME managers not to give up easily and continue to improve their quality so that the resulting products will be more competitive.